Prey type and foraging ecology of Sanderlings Calidris alba in different climate zones: are tropical areas more favourable than temperate sites? - Grond, Kirsten; Ntiamoa-Baidu, Yaa; Piersma, Theunis; Reneerkens, Jeroen (My University, 2015)
Sanderlings (Calidris alba) are long-distance migratory shorebirds with a non-breeding range that spans temperate and tropical coastal habitats. Breeding in the High Arctic combined with non-breeding seasons in the tropics necessitate long migrations, which are energetically demanding. On an annual basis, the higher energy expenditures during migration might pay off if food availability in the tropics is higher than at temperate latitudes. We compared foraging behaviour of birds at a north temperate and a tropical non-breeding site in the Netherlands and Ghana, respectively. In both cases the birds used similar habitats (open beaches), and experienced similar periods of daylight, which enabled us to compare food abundance and availability, and behavioural time budgets and food intake. During the non-breeding season, Sanderlings in the Netherlands spent 79% of their day foraging; in Ghana birds spent only 38% of the daytime period foraging and the largest proportion of their time resting (58%). The main prey item in the Netherlands was the soft-bodied polychaete Scolelepis squamata, while Sanderlings in Ghana fed almost exclusively on the bivalve Donax pulchellus, which they swallowed whole and crushed internally. Average availability of polychaete worms in the Netherlands was 7.4 g ash free dry mass (AFDM) m−2, which was one tenth of the 77.1 g AFDM m−2 estimated for the beach in Ghana. In the tropical environment of Ghana the Sanderlings combined relatively low energy requirements with high prey intake rates (1.64 mg opposed to 0.13 mg AFDM s−1 for Ghana and the Netherlands respectively). Although this may suggest that the Ghana beaches are the most favourable environment, processing the hard-shelled bivalve (D. pulchellus) which is the staple food could be costly. The large amount of daytime spent resting in Ghana may be indicative of the time needed to process the shell fragments, rather than indicate rest.
Citation: Grond, K., Ntiamoa-Baidu, Y., Piersma, T., & Reneerkens, J. (2015). Prey type and foraging ecology of Sanderlings Calidris alba in different climate zones: are tropical areas more favourable than temperate sites? PeerJ, 3, e1125. https://doi.org/10.7717/peerj.1125
Keywords: Benthic invertebrates; Shorebirds; Time budgets; Energy budgets; Differential migration; Migration